2010
DOI: 10.1038/ismej.2010.176
|View full text |Cite
|
Sign up to set email alerts
|

Novel Clostridium populations involved in the anaerobic degradation of Microcystis blooms

Abstract: Understanding the microbial degradation of Microcystis biomass is crucial for determining the ecological consequences of Microcystis blooms in freshwater lakes. The purpose of this study was to identify bacteria involved in the anaerobic degradation of Microcystis blooms. Microcystis scum was anaerobically incubated for 90 days at three temperatures (15 1C, 25 1C and 35 1C). We used terminal restriction fragment length polymorphism (T-RFLP) analysis of bacterial 16S rRNA genes, followed by cloning and sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 45 publications
3
35
0
Order By: Relevance
“…2). The C. histolyticum group consists of cluster I and II of the Clostridiaceae including many species with pathogenic potential [47]. Therefore, the glyphosate-induced dysbiosis of crude fiberrich diets during the dry period of cows could induce a higher susceptibility for pathogens or support such microorganisms that normally occur in small numbers.…”
Section: Discussionmentioning
confidence: 99%
“…2). The C. histolyticum group consists of cluster I and II of the Clostridiaceae including many species with pathogenic potential [47]. Therefore, the glyphosate-induced dysbiosis of crude fiberrich diets during the dry period of cows could induce a higher susceptibility for pathogens or support such microorganisms that normally occur in small numbers.…”
Section: Discussionmentioning
confidence: 99%
“…During the post-blooming stage, large quantities of algae cells accumulate and decompose, resulting in serious environmental and ecological consequences (Li et al, 2012). Recent studies have shown that various heterotrophic bacteria are associated with algal blooms and decomposition in eutrophic lakes (Berg et al, 2009;Grossart et al, 2006;Xing et al, 2011). Taihu lake, located in Jiangsu Province of China (30 u 559 400-31 u 329 580 N 119 u 529 320-120 u 369 100 E), has suffered from repeated algal blooms in the past years (Paerl et al, 2011).…”
mentioning
confidence: 99%
“…Taihu lake, located in Jiangsu Province of China (30 u 559 400-31 u 329 580 N 119 u 529 320-120 u 369 100 E), has suffered from repeated algal blooms in the past years (Paerl et al, 2011). Previous studies on the microbial diversity and population dynamics during algal decomposition with molecular tools such as 16S rRNA gene sequencing showed that Clostridium-affiliated 16S rRNA gene sequences from members of the phylum Firmicutes were highly abundant in decomposing algal slurry (Xing et al, 2011). We attempted to cultivate bacterial isolates, and bacterial strains that are phylogenetically related to the genus Paenibacillus of the phylum Firmicutes were obtained.…”
mentioning
confidence: 99%
“…Besides, redox potential also affected anaerobic fermentation process [32]. It was reported that CBB was anaerobically degraded mainly through fermentation by the genus Clostridium [33]. In fact, the genus Clostridium is widely regarded as important fermentative bacteria [34].…”
Section: Discussionmentioning
confidence: 99%